Natural Convection in a Cylindrical Cavity Heated by an Internally-Located Strong Source - Słomczyńska, J. (Engineering Transactions, 1993)
Stationary natural! convection caused by a strong source of beat centrally located in a cylindrical cavity is analyzed by a finite-difference method. Since gradients of pressure are much smaller than gradients of both the temperature and density, the axisymmetric flow is treated as incompressible while, for the same reason, variable density is fully accounted for. Viscosity and thermal conductivity are assumed to be functions of temperature. Coupled stationary equations of continuity, motion, and energy are formulated in the framework of primitive variables. Line integration of the equation of motion over a closed contour is used to eliminate pressure. The solution, i.e. temperature (hence, density) and velocity distributions in the cavity, is found by a two-step iterative procedure based on line successive overrelaxation, Examples of computation showing the effects of change in the source heat-rate, mean value of pressure and the aspect ratio of the cavity are provided.